A Synthetic MUC1 Glycopeptide Bearing βGalNAc‐Thr as a Tn Antigen Isomer Induces the Production of Antibodies against Tumor Cells. (14th February 2017) - Leiria Campo, Vanessa; Riul, Thalita B.; Oliveira Bortot, Leandro; Martins‐Teixeira, Maristela B.; Fiori Marchiori, Marcelo; Iaccarino, Emanuela; Ruvo, Menotti; Dias‐Baruffi, Marcelo; Carvalho, Ivone
Abstract: This study presents the synthesis of the novel protected O‐glycosylated amino acid derivatives1 and2, containing βGalNAc‐SerOBn and βGalNAc‐ThrOBn units, respectively, as mimetics of the natural Tn antigen (αGalNAc‐Ser/Thr), along with the solid‐phase assembly of the glycopeptides NHAcSer‐Ala‐Pro‐Asp‐Thr[αGalNAc]‐Arg‐Pro‐Ala‐Pro‐Gly‐BSA (3 ‐BSA) and NHAcSer‐Ala‐Pro‐Asp‐Thr[βGalNAc]‐Arg‐Pro‐Ala‐Pro‐Gly‐BSA (4 ‐BSA), bearing αGalNAc‐Thr or βGalNAc‐Thr units, respectively, as mimetics of MUC1 tumor mucin glycoproteins. According to ELISA tests, immunizations of mice with βGalNAc‐glycopeptide4 ‐BSA induced higher sera titers (1:320 000) than immunizations with αGalNAc‐glycopeptide3 ‐BSA (1:40 000). Likewise, flow cytometry assays showed higher capacity of the obtained anti‐glycopeptide4 ‐BSA antibodies to recognize MCF‐7 tumor cells. Cross‐recognition between immunopurified anti‐βGalNAc antibodies and αGalNAc‐glycopeptide and vice versa was also verified. Lastly, molecular dynamics simulations and surface plasmon resonance (SPR) showed that βGalNAc‐glycopeptide4 can interact with a model antitumor monoclonal antibody (SM3). Taken together, these data highlight the improved immunogenicity of the unnatural glycopeptide4 ‐BSA, bearing βGalNAc‐Thr as Tn antigen isomer. Abstract : Anticancer immunogenicity : Glycopeptides incorporating αGalNAc‐Thr (Tn) and βGalNAc‐Thr residues as Tn antigen isomers were synthesized as mimetics of MUC1 tumor mucin glycoproteins. The unnatural βGalNAc‐glycopeptide‐BSA showed improved immunogenicity, with potential for the development of anticancer vaccines.